RELATIONSHIP OF AGE AND NUTRITION STATUS WITH WORK FATIGUE IN INPATIENT NURSES AT DR M YUNUS HOSPITAL, BENGKULU - Rina Aprianti; Susilo Wulan; Elza Wulandari (LPPM Politeknik Kesehatan Kerta Cendekia, 2021)
Background: Nurse is a profession that cannot be separated from the problem of work fatigue. Fatigue due to work will have a negative impact on work such as decreased accuracy, skill, and even work productivity. If this happens to nurses, it can put the patient at risk, decreasing the quality of service. Work fatigue is caused by several factors, such as worker characteristics, namely age, sex, education, nutritional status, and work environment factors (Tarwaka, 2013). Nurses have a fairly heavy duty in assisting emergency services and nursing services continuously for 24 hours so that nurses sometimes eat irregularly which can cause nutritional conditions to be disturbed (Astuti, Ekawati, & Wahyuni, 2017). Objectives: The purpose of this study was to determine the relationship between age, nutritional status and subjective work fatigue in inpatient nurses at dr. M Yunus Bengkulu. Methods: The research design was an analytic survey with a cross sectional approach. The population of this study were 128 nurses in the inpatient room with total sampling technique. The data collection instrument is a work fatigue feeling questionnaire consisting of 17 questions adopted from (Setyawati, 2010) which has tested the validity and reliability in her book entitled at a glance about work fatigue, a nutritional status questionnaire by taking physical measurements of body weight and height to determine BMI, and age questionnaire with units of years. Data analysis used chi square test with 95% degree of error if p-value ? 0.05 indicates a significant relationship and if > 0.05 is not significant. Results: This study shows that there is no relationship between age and subjective work fatigue on nurses with a p-value = 0.107 > ? = 0.05. And there is a relationship between nutritional status and subjective work fatigue on nurses with a p-value = 0.000 > ? = 0.05. Conclusion: Work fatigue that occurs in nurses is expected to be an important concern, nurses should maintain a healthy body by consuming balanced nutritious food and diligent exercise and adequate rest, so as to reduce the risk of fatigue due to work.